Epigenetic and parasitological parameters are modulated in EBi3-/- mice infected with Schistosoma mansoni - Ester Alves Mota; Andressa Barban do Patrocínio; Vanderlei Rodrigues; João S. Silva; Vanessa Carregaro; Renata Guerra‐Sá (2020)
Schistosoma mansoni adaptive success is related to regulation of replication, transcription and translation inside and outside the intermediate and definitive host. We hypothesize that S. mansoni alters its epigenetic state in response to the mammalian host immune system, reprogramming gene expression and altering the number of eggs. In response, a change in the DNA methylation profile of hepatocytes could occurs, modulating the extent of hepatic granuloma. To investigate this hypothesis, we used the EBi3-/- murine (Mus musculus) model of S. mansoni infection and evaluated changes in new and maintenance DNA methylation profiles in the liver after 55 days of infection. We evaluated expression of epigenetic genes and genes linked to histone deubiquitination in male and female S. mansoni worms. Comparing TET expression with DNMT expression indicated that DNA demethylation exceeds methylation in knockout infected and uninfected mice and in wild-type infected and uninfected mice. S. mansoni infection provokes activation of demethylation in EBi3-/-I mice (knockout infected). EBi3-/-C (knockout uninfected) mice present intrinsically higher DNA methylation than WTC (control uninfected) mice. EBi3-/-I mice show decreased hepatic damage considering volume and reduced number of granulomas compared to WTI mice; the absence of IL27 and IL35 pathways decreases the Th1 response resulting in minor liver damage. S. mansoni males and females recovered from EBi3-/-I mice have reduced expression of a deubiquitinating enzyme gene, orthologs of which target histones and affect chromatin state. SmMBD and SmHDAC1 expression levels are downregulated in male and female parasites recovered from EBi3-/-, leading to epigenetic gene downregulation in S. mansoni. Changes to the immunological background thus induce epigenetic changes in hepatic tissues and alterations in S. mansoni gene expression, which attenuate liver symptoms in the acute phase of schistosomiasis.